Severity of arterial and/or arteriolar sclerosis in IgA nephropathy and the effects of renin–angiotensin system inhibitors on its prognosis. (29th June 2021) - Sugiura, Naoko; Moriyama, Takahito; Miyabe, Yoei; Karasawa, Kazunori; Nitta, Kosaku
Abstract: IgA nephropathy (IgAN) patients often suffer from arterial and/or arteriolar sclerosis (AAS); however, it is unclear whether these features are associated with a poor prognosis. This retrospective cohort study aimed to analyse the prognosis of IgAN patients with AAS and assess whether treatment with renin–angiotensin system inhibitors (RASI) improved their survival. The study included 678 IgAN patients, who were grouped into AAS0 ( n  = 340; AAS absent) and AAS1 ( n  = 338; AAS present) groups. Each patient's clinical, laboratory, and histological backgrounds and 20‐year renal prognosis were analysed. In the AAS1 group, the impact of RASI initiated during the follow‐up period on the renal prognosis was also evaluated after adjustments for background characteristics. IgAN patients with AAS had significantly higher age, blood pressure, body mass index, total cholesterol, uric acid levels, and proteinuria than patients without AAS; they also had more severe histological findings, decreased renal function, and lower survival rates than those without AAS (64.0 versus 84.7%, p  < 0.001). Multivariate Cox regression analysis incorporating clinical and histological findings and treatments revealed AAS as an independent factor for disease progression (hazard ratio: 2.23, p  = 0.010). Participants in the AAS1 group treated with RASI during follow‐up had a significantly higher renal survival rate than those who were not (75.5 versus 44.3%, p  = 0.013). In conclusion, AAS was found to be associated with serious clinical, laboratory, and histological findings and poor prognosis. RASI initiated during the follow‐up period was found to improve renal prognosis.